Strengthening Pancasila Values During the Covid-19 Pandemic - Jagad Aditya Dewantara; T Heru Nurgiansah (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
Pancasila is a guideline for Indonesians in carrying out their daily lives. Since 2020 Indonesia is in the covid-19 pandemic. The purpose of this study is to know and analyze the strengthening of Pancasila values during the Covid-19 pandemic. The method used is a qualitative descriptive approach with data collection techniques through observation, interview, documentation, and literacy. The results of the research showed that the values of Pancasila should be strengthened in the face of the Covid-19 Pandemic in Indonesia. The strengthening of Pancasila value is reflected in the application of health protocols, namely, diligently washing hands, always wearing masks, maintaining distance, avoiding crowds, and refraining from the mobility of time. If the implementation of the health protocol is implemented properly then it is in line with the values contained in pancasila